The effect of credit and liquidity risk management practices on the profitability ratios of selected Philippine thrift banks - Canlas, Renee Ysobelle S. (Animo Repository, 2022)
Financial institutions have an important role in a country’s economy since financial institutions contribute to economic growth with various factors such as profit. However, banks encounter several risks compared to other industries. Banks are always concerned with two major factors which are liquidity and solvency in order to avoid any bank failures or crises. This research then aims to analyze the effect of credit and liquidity risk management practices on the profitability ratios of 7 selected thrift banks in the Philippines from 2016 to 2020. Regression analysis was used to analyze the effect and relationship of the risk management practices on profitability ratios. For this research, six different statistical tests were used to prove the hypotheses presented in this study, mainly Pearson Correlation Coefficient and T-Test. Using these different statistical tests and ratios, the study was able to find that Capital Adequacy Ratio (credit risk) and Cash-to-Deposit Ratio have a significant impact and Capital Adequacy Ratio (credit risk) and Loan-to-Deposit Ratio have a significant relationship with profitability. In contrast, Non-performing Loans and Loan-to-Deposit Ratios have an insignificant impact and Non-performing Loans and Cash-to-Deposit Ratios have an insignificant relationship with profitability. This proves that credit risk management and liquidity risk management practices are important factors in determining a bank's profitability and avoiding bank failure.